Sorrow for books: What did the compilers of 16th-century autobibliographies worry about? - M. L. Sergeev (Шаги, 2023)
The article examines a type of “autobiographical sadness” — the author’s feelings associated with the creation and publication of books. Varied manifestations of self-reflection and emotions are found in texts of the autobibliographic genre, which flourished in the era of humanism and early printing. The synthesisof bibliography and biography, which had Greek and Roman prototypes and was characteristic, among others, of humanist handbooks in bibliography, contributed to the explicit expression of the authorial “self” in such seemingly technical, dry and “objective” works. The very structure of these handbooks implied the inclusion of an article about its compiler in the text. In this article, two examples of such texts are analyzed — namely, the autobibliographies by the Swiss polymath Conrad Gessner and by the English clergyman and historian John Bale. Written only three years apart (in 1545 and 1548, respectively), they nevertheless differ significantly, in both the organization of the biographical narrative and in the nature of book presentation. The article shows that the peculiarity of these texts is largely due to differences in the self-identification and self-presentation of their authors. While for Bale the acquisition of the true faith and confessional polemics were of fundamental importance, Gessner, though also a Protestant, places his own formation as a humanist author and interaction with book publishers in the focus of the story.